A forgotten pioneer: Eugene Marteney and the American renaissance of hautboy-making, 1962–1969. (14th July 2022) - Howe, Robert
Abstract: Coming from a background in science and philosophy, the American electrical engineer Eugene Marteney (1934–2008) stumbled into hautboy-making in 1961–2, inspired by the playing of Josef Marx. Marteney learned the techniques of woodwind manufacture from Friedrich von Huene, who ultimately referred potential buyers to him. Selling hautboys after 1964, he did everything himself, from measuring antique specimens to designing and making the instruments and their reeds. He made connections with Marx, von Huene, Bruce Haynes, Paul Hailperin and, through him, with Michel Piguet and Bernhard Schermer, which would set off modern hautboy-making at original pitches. Marteney did this all half a decade before anyone else. In so doing he influenced all of the people we remember today as modern hautboy pioneers, laying the foundations for the Baroque revival of the 1970s and 80s. In 1969, as Schermer and Haynes started making quality hautboys at original pitches, Marteney stopped doing so. His work was then forgotten until 2010. This article explores the hautboy-making of this remarkable man and shows how he influenced more well-known figures.